The Persistence of HIV Risk Behaviors Among Methamphetamine-Using Offenders() - Cartier, Jerome J. (2008)
Studies have shown that methamphetamine (MA) is rapidly becoming the drug of choice for a large number of substance-abusing offenders and is associated with significantly higher levels of HIV risk behaviors prior to their incarceration. Despite these findings, there has been little follow-up research to determine whether these patterns persist among recently paroled offenders after attendance in an in-prison treatment program. This study uses the self-reported data from 812 substance-abusing offenders in a multisite NIDA-funded project to determine whether, either before incarceration or nine months after release from an in-prison substance abuse program, MA use in the past 30 days was associated with increased HIV risk behaviors. The findings indicate that offenders who used MA prior to and after incarceration and treatment report higher levels of HIV risk behaviors compared with offenders with no MA use. Clinical and policy implications of the findings are discussed.